The Influence of the Student Team Achievement Division (STAD) Cooperative Learning Model on Student Learning Motivation and Mathematical Reasoning Ability of Class V Students of SDN 10 Rupat - Nursatia Saruksuk; Masrul; Kasman Ediputra (Institute of Educational, Research, and Community Service, 2024)
This study aims to examine the influence of the cooperative learning model type Student Team Achievement Division (STAD) on the learning motivation and mathematical reasoning ability of fifth-grade students at SDN 10 Rupat. The method used in this research is an experimental method with a pretest-posttest design. The research sample consisted of 17 fifth-grade students. During the study, the STAD learning model was implemented, and data were collected through pretests and posttests to measure students' learning motivation and mathematical reasoning ability. The results of the study showed a significant increase in students' learning motivation, with an average pretest score of 67.24 and a posttest score of 80.06. Students' mathematical reasoning ability also significantly improved, from an average pretest score of 59.88 to a posttest score of 73.71. The hypothesis testing, which included the Paired T-Test, yielded significant results (p < 0.05), indicating that the STAD learning model is effective in enhancing students' learning motivation and mathematical reasoning ability. Thus, the STAD learning model can be considered an effective method for teaching mathematics at the elementary school level.